Negative workplace gossip and turnover intention among Chinese rural preschool teachers: The mediation of ego depletion and the moderation of bianzhi - He, Can; Wei, Hua (Frontiers in Psychology, 2022)
Abstract: In China, the high turnover rates of teachers have become one of the biggest obstacles to the development of rural preschool education. Based on the social information processing theory and the strength model of self-control, this study examined the relationship between negative workplace gossip and turnover intention and the role of ego depletion and bianzhi in this relationship. The questionnaire method was applied, and 411 rural preschool teachers in Hubei Province, China, participated in the survey. The correlation results showed that negative workplace gossip was positively correlated with ego depletion, and ego depletion was positively correlated with turnover intention. After controlling for age, negative workplace gossip positively predicted turnover intention. The mediation analysis indicated that ego depletion played a mediating role in the relationship between negative workplace gossip and turnover intention. Moreover, the mediation effect was moderated by bianzhi. Negative workplace gossip had a stronger effect on the ego depletion of teachers without bianzhi than on that of teachers with bianzhi. The current research is the first to clarify that ego depletion mediates the relationship between negative workplace gossip and turnover intention, and the mediation effect is moderated via bianzhi. These findings expand our understanding of the influential factors and formation mechanisms of turnover intention. In practice, this study provides a novel perspective for policymakers and administrators to reduce the turnover intention among rural preschool teachers in China.